The 18-cm Thoracic-Height Threshold and Pulmonary Function in Non-Neuromuscular Early-Onset Scoliosis - Charles E. Johnston, MD (Wolters Kluwer, 2021)
Background:. Thoracic spine height is cited as a crucial outcome measure in the treatment of early-onset scoliosis (EOS) because of its reported relationship to pulmonary function tests (PFTs). An 18-cm threshold has been proposed, although this single parameter might be overly simplistic for cases of different etiologies and deformity magnitude. We aimed to reevaluate pulmonary function in patients undergoing corrective surgery, assessing the role of residual scoliosis as well as spine elongation Methods:. Patients undergoing EOS correction with a minimum of 5 years of follow-up since initial treatment were evaluated. Standard spirometry (forced vital capacity [FVC], forced expiratory volume in 1 second [FEV1]) was correlated to deformity magnitude and T1-T12 height. Patients were compared by age at first surgery (<5 or ≥5 years), final thoracic height (≤18 or >18 cm), and percentage of predicted pulmonary function (<60% or ≥60%). Results:. Twenty-nine patients (15 congenital, 11 syndromic, and 3 idiopathic cases) were tested at a mean of 8.5 years following initial surgery. Twenty-two patients (mean initial age, 4.8 years) had growth-sparing instrumentation, and 7 patients (age, 5.1 years) had definitive fusion performed. Age at initial surgery was not associated with a difference in PFT results at the time of follow-up, and both age groups had ominously low percentages of predicted pulmonary-function volumes (50% to 55%). Only 18 of the 29 patients achieved a T1-T12 height of >18 cm. Those with a thoracic height of ≤18 cm had similar percentage-of-predicted spirometry results at the time of follow-up as those with greater thoracic height, possibly because of increased deformity correction. Only 14 of 29 patients had spirometry of ≥60% of predicted volume at the time of follow-up. These 14 had slightly smaller curves and slightly greater T1-T12 heights but significantly better spirometry results than the 15 subjects with <60% of predicted volume. For those with a T1-T12 height of ≤18 cm, the residual Cobb angle negatively correlated with spirometry results. In those with a final T1-T12 height of >18 cm, spirometry did correlate with thoracic height, especially when residual deformity was ≥60°. Conclusions:. Regardless of thoracic height of ≤18 or >18 cm, with residual curves of >50o, pulmonary function was ominously low in fully half of the patients, raising doubt about the value of this threshold as an EOS outcome parameter. Level of Evidence:. Prognostic Level IV. See Instructions for Authors for a complete description of levels of evidence.